IMPLEMENTASI STRATEGI GURU DALAM MENGATASI KESULITAN BELAJAR SISWA KELAS V DI SD MUHAMMADIYAH 1 LIMBOTO KECAMATAN LIMBOTO KABUPATEN GORONTALO - Nursulistiowati; Yulanti S. Mooduto; Nursyaidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of teachers’ strategies in addressing elementary students’ learning difficulties. The research problem originates from the persistent occurrence of students’ learning difficulties, which are indicated by low learning motivation, limited understanding of the subject matter, and variations in students’ abilities and learning styles. This study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure data validity. The findings reveal that teachers’ strategies in overcoming learning difficulties are implemented through four main stages: identification of learning difficulties, differentiated instructional planning, implementation of adaptive teaching methods, and continuous evaluation and reflection. These strategies have been shown to enhance students’ engagement, improve their understanding of the material, and increase their confidence in the learning process.These findings highlight that adaptive and student-centered instructional strategies play a crucial role in addressing learning difficulties in elementary education.